2018
DOI: 10.1177/1758834018755090
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of anti-VEGF drug-induced hypertension using different hypertension criteria: a secondary analysis of the COMPARZ study

Abstract: Background:There is inconsistency in the criteria used to define anti-vascular endothelial growth factor (VEGF) drug-induced hypertension (AVEGF-HT) in published studies. It is unknown whether specific patient characteristics similarly predict AVEGF-HT using different criteria.Methods:We assessed the associations between clinical and demographic factors (n = 22) and AVEGF-HT, using six criteria based on predefined on-treatment blood pressure (BP) thresholds or absolute BP elevations versus baseline, in a post … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…The trial did not reach the primary endpoint of achieving lower than grade 3 AEs for fatigue, diarrhea, and HFS in patients on schedule 2/1; however, the investigators reported similar rates (∼25%) of these grade 3 AEs as has been historically reported for patients on schedule 4/2. In addition, they noted that no grade 4 AEs were reported for patients on schedule 2/1 and the discontinuation rate for patients was 10%, which compares favorably with the original pivotal trial data reported by Motzer and colleagues (2007) and the more recent COMPARZ trial data, wherein the discontinuation rates were 20% for patients on schedule 4/2 ( Jonasch et al, 2018 ; Mangoni, Kichenadasse, Rowland, & Sorich, 2018 ). Jonasch and colleagues also reported efficacy results (median progression-free survival of 13.7 months; 95% confidence interval = 10.9–16.3 months) that were better than expected based on the prognostic classifications of the patient population (78% of patients were intermediate- or poor-risk according to Memorial Sloan Kettering Cancer Center criteria; Jonasch et al, 2018 ), suggesting that, at the least, schedule 2/1 is not associated with a reduction in efficacy ( Mangoni et al, 2018 ).…”
Section: Discussionsupporting
confidence: 72%
“…The trial did not reach the primary endpoint of achieving lower than grade 3 AEs for fatigue, diarrhea, and HFS in patients on schedule 2/1; however, the investigators reported similar rates (∼25%) of these grade 3 AEs as has been historically reported for patients on schedule 4/2. In addition, they noted that no grade 4 AEs were reported for patients on schedule 2/1 and the discontinuation rate for patients was 10%, which compares favorably with the original pivotal trial data reported by Motzer and colleagues (2007) and the more recent COMPARZ trial data, wherein the discontinuation rates were 20% for patients on schedule 4/2 ( Jonasch et al, 2018 ; Mangoni, Kichenadasse, Rowland, & Sorich, 2018 ). Jonasch and colleagues also reported efficacy results (median progression-free survival of 13.7 months; 95% confidence interval = 10.9–16.3 months) that were better than expected based on the prognostic classifications of the patient population (78% of patients were intermediate- or poor-risk according to Memorial Sloan Kettering Cancer Center criteria; Jonasch et al, 2018 ), suggesting that, at the least, schedule 2/1 is not associated with a reduction in efficacy ( Mangoni et al, 2018 ).…”
Section: Discussionsupporting
confidence: 72%
“…The introduction of vascular endothelial growth factor (VEGF) inhibitors (also known as antiangiogenics) and checkpoint inhibitors for advanced cases of RCC has significantly impacted the survival of these patients (39)(40)(41)(42). The Food and Drug Administration (FDA) approval of sorafenib and sunitinib in 2005 and 2006, respectively, followed by the approval of more antiangiogenic therapies have been a pivotal point in advanced RCC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Preexisting HTN, older age, and obesity were risk factors for increased blood pressure after VSP inhibitor administration. 42,43 Half the patients with 2 of the above risk factors and 60% of those with all 3 risk factors developed HTN after anti-VEGF therapy. 42 In the present study, 62% of the total study population and >70% of those with preexisting HTN were aged ≥70 years, and the age distribution in the present study was higher than in other clinical trials.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%